A 1, 8-naphthalimide-based chemosensor for dual-mode sensing: colorimetric and fluorometric detection of multiple analytes. Issue 87 (5th September 2016) - La, Yeo-Kyung; Hong, Jong-Ah; Jeong, Yu-Jin; Lee, Jiyoun
Abstract : A dual-mode sensor1 demonstrated highly specific and sensitive signal changes to multiple analytes based on two distinct mechanisms. Abstract : We designed a 1, 8-naphthalimide-based chemosensor for dual-mode sensing of multiple analytes. Sensor1 contains a hydrazone linker with a quinoline group that can generate CN − and F − -specific color changes while exhibiting Hg 2+ -specific fluorescence enhancement. Sensor1 demonstrated highly specific and sensitive signal changes upon binding to these ions with detection limits in the submicromolar range. We believe that sensor1 responds to anions and cations by two distinct mechanisms, thus enabling dual-mode detection of multiple analytes.